Beginnings and beyond - Gordon, Ann Miles; Browne, Kathryn Williams (Albany, N.Y. : Delmar, 2000)
What is the field of early childhood education? Who is the young child? Who are the teachers? What is the setting? What is being taught? How do we teach for tomorrow?
Keywords: Education; Child development; Curricula; Early childhood education; Child development; Early childhood education -- Curricula; Education -- Early childhood education